Administrative and Legal Protection of the Rights of Cosmetological Services’ Consumers - V. І. Teremetskyi; A. I. Sadovenko (Bulletin of Kharkiv National University of Internal Affairs)
The purpose of the study is to define the concept and content of administrative and legal protection of the rights of consumers of cosmetological services, as well as to develop propositions to improve domestic legislation in this area.